PENGATURAN SISTEM ELEKTRONIK DALAM PENGAMBILAN KEPUTUSAN RAPAT UMUM PEMEGANG SAHAM (RUPS) PERSEROAN TERBATAS YANG BERKEPASTIAN - Komang Febrinayanti Dantes (Jurnal Komunikasi Hukum, 2022)
This study aims to determine and analyze the rules in the event of the General Meeting of Shareholders conducted electronically. Events in the General Meeting of Shareholders which are conducted using an electronic system where the shareholders cannot meet face-to-face directly, but face-to-face with the media provided by the institution providing the electronic GMS. This incident created a gap for shareholders to deny the results of the decision of the General Meeting of Shareholders electronically, because the electronic GMS was included in the category of a mere fact (circumstances) which was temporary. So it is very necessary to have strict rules regarding its implementation. The Financial Services Authority then issued the Financial Services Authority regulations POJK 15 and POJK 16 which can bridge and make the implementation of the GMS electronically based on law and are not easy to be denied as a legal act from the shareholders on the statement of their will. The shareholders in the electronic implementation of the GMS make a separate statement, fingerprint, and electronic signature which have been clearly regulated in the Information and Electronic Transaction Law Number 16 of 2019 on the amendments to Law Number 11 of 2008 and also refer to in Article 77 of Law Number 40 of 2007 concerning Limited Liability Companies.